Religion on the move!: new dynamics of religious expansion in a globalizing world - Adogame, Afeosemime Unuose; Shankar, Shobana (International studies in religion and society, 2013)
Preliminary Material -- Introduction: Exploring New Frontiers in Global Religious Dynamics /Afe Adogame and Shobana Shankar -- 1 Pax et Securitas: The Problematic Missional Role of Theopolitical Rhetoric in the Contexts of Globalization and Terror /Matthew Forrest Lowe -- 2 Ignoring the East: Correcting a Serious Flaw in World Christianity Scholarship /Dyron B. Daughrity -- 3 Southern Saints and their Northern Siblings: Christians Crossing Boundaries through Sister Church Relationships /Janel Kragt Bakker -- 4 The Church Mission Society and Reverse Mission: From Colonial Sending to Postcolonial Partnership and Reception /Rebecca Catto -- 5 Indigenization, Syncretism and the Assumed Boundedness of Christianity: A Critique /Jonas Adelin Jørgensen -- 6 Syncretism of Christian samurai at the Kumamoto Band in Japan: Fulfillment of Confucianism in Christianity /Shuma Iwai -- 7 Exploring the South—South Trajectory of Global Religious Flows: The Origins of Ghana’s Hinduism /Albert Wuaku -- 8 Door to Door Daʿwa in Africa: Dynamics of Proselytization in Yan Izala and Tablīghī Jamāʿat /Hakano Abdi Wario and Ramzi Ben Amara -- 9 Korean Missionaries: Preaching the Gospel to “All Nations,” including the United States /Rebecca Y. Kim -- 10 Religion in Motion: A Missionary Narrative of Creativity and Survival from the Pentecostal Nigerian Diaspora in Italy /Annalisa Butticci -- 11 Mobilizing Gender around the Globe: The Ecumenical Movement as a Resource for gender Equity in Arab Christianity /Heidemarie Winkel -- 12 Towards a Global Sisterhood: The Transnational Activities of the Federation of Muslim Women’s Associations in Nigeria /Olufunke Adeboye -- 13 Localizing Christianity for Social Change: The Subversion of Caste in Rural South India /Anderson H. M. Jeremiah -- 14 Local Revival and Global Expansion: The Case of African Christianity /Mark Shaw -- 15 The Shifting Map of Religious Proclivity in Brazil, and How the Media Prospect is Seemingly Unable to Deal with It /Marilia Fiorillo -- 16 Dynamics of Islamic Religious Movements in Nigeria: A Case Study of Nasru-Lahil-Fatih Society of Nigeria /Musa. O. Adeniyi -- 17 New Dynamics of Christian Expansion: Boundary Crossing in the Mission of Immigrant Churches in the Netherlands /Daniëlle Koning -- 18 Expanding Boundaries of Recognition and Mobility?—Otherworldly Rhetoric and This-worldly Organisation in an African based Charismatic Church in Germany /Susanne Kröhnert-Othman -- 19 Migration and the Growth of Evangelical Christianity: An Ethnographic Study in Cuernavaca, Mexico /Philip Wingeier-Rayo -- 20 The Politicization of Religious Identity in Sudan, with Special Reference to Oral Histories of the Sudanese Diaspora in America /Matthew Kustenbauder -- 21 Reverse Evangelization: Pentecostal Imagination and Mobilization of Identity in the French Migrant Context /Damien Mottier -- 22 Local Relevance and Global Appeal: Nigerian Female Religious Leaders in London: Case Study of Lady Evangelist/ Prophetess Lizzy Adedamola a. k. a. Alhaja Jesu, Founder of Gospel Light Evangelical Ministry /Bolaji Bateye -- Contributors -- Index.